2019
DOI: 10.1186/s13287-019-1301-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: BMP2 secretion from hepatocellular carcinoma cell HepG2 enhances angiogenesis and tumor growth in endothelial cells via activation of the MAPK/p38 signaling pathway

Abstract: Background Hepatocellular carcinoma (HCC) is one of the most common tumors globally, with varying prevalence based on endemic risk factors. Bone morphogenetic protein (BMP) exhibits a broad spectrum of biological activities in various tissues including angiogenesis. Here, this study aimed to investigate the mechanism of BMP2 in HCC by mediating the mitogen-activated protein kinase (MAPK)/p38 signaling pathway. Methods BMP2 expression was quantified in HCC and adjacent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Silencing BMP2 helps to prevent HCC cell migration and invasion. 22 In conclusion, BMP2 knockdown inhibited the EMT and then the invasion and migration of CSCs in HCC.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Silencing BMP2 helps to prevent HCC cell migration and invasion. 22 In conclusion, BMP2 knockdown inhibited the EMT and then the invasion and migration of CSCs in HCC.…”
Section: Discussionmentioning
confidence: 83%
“…In agreement with this, a previous study has also demonstrated the abnormal upregulation of BMP2 in HCC. 22 CSCs, showing presence in primary cancers, are identified to drive cancer growth with the potent self-renewing ability, and consequently targeting CSCs has been recognized as a promising therapy for cancer treatment. 25 Compared with HepG2 and SMMC7721 cells, HepG2-CSCs and SMMC7721-CSCs showed dramatically increased sphere formation rate and colony numbers, and markedly elevated levels of CSC markers (CD44 and ALDH1) and pluripotent transcription factors (Bmil, SOX2 and OCT4), demonstrating the stemness of HepG2-CSCs and SMMC7721-CSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different kinds of angiogenic factors, bone morphogenetic protein 2 (BMP2) has been proven to be valuable. Studies have shown that BMP2 could regulate the promotion of cell angiogenesis, proliferation, and migration via the p38 signaling pathway [ 23 ]. Besides, studies also have shown that BMP2 could promote vascularization and was involved in tumorous angiogenesis possibly through Id1 and p38 MAPK pathways, for example, BMP2 had effects on the angiogenesis of hepatocellular carcinoma [ 17 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of the EGFR-RAS-MAPK pathway leads to dysregulated cell proliferation in HCC [113] . The MAPK/p38 signaling has been shown to promote angiogenesis and drive tumor cell metastasis (migration and invasion) [114,115] . In addition, activation of the MAPK/p38 endows resistance against apoptosis to HCC cells [116] .…”
Section: Endothelial Cellsmentioning
confidence: 99%